Estimating damages from price-fixing: The value of transaction data - Kai Hüschelrath; Kathrin Müller; Tobias Veith (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
We use a unique private data set of about 340,000 invoice positions from 36 smaller and larger customers of German cement producers to study the value of such transaction data for an estimation of cartel damages. In particular, we investigate, first, how structural break analysis can be used to identify the exact end of the cartel agreement and, second, how an application of before-and-after approaches to estimate the price overcharge can benefit from such rich data sets. We conclude that transaction data allows such a detailed assessment of the cartel and its impact on direct customers that its regular application in private antitrust cases is desired as long as data collection and preparation procedures are not prohibitively expensive.
Keywords: 330; antitrust policy; private enforcement; cartels; overcharge; damages; cement; Zementindustrie; Kartell; Zement; Preis; Umsatz; Soziale Kosten; Schätzung; Deutschland